An Exploratory Study of Positioning of Cement Brands in Rajasthan - Prasad, S. Shyam; Rathore, Vishwajeet Singh; Kathawala, Aslam Ahmed (Indian Journal of Marketing, 2019)
This study was undertaken during April - July 2018 in order to understand the brand positioning of cement brands and consumer behaviour in buying cement in Rajasthan, India. The present literature has very few papers on the topic of cement brands. From an initial set of 15 brands, a set of nine brands were chosen for analysis after an exploratory survey. The brands selected for analysis were Ambuja, UltraTech, Shree, JK, Binani, Nirmax, Wonder, Birla, and Coromandel cement brands. The multidimensional scaling (MDS) technique was used to plot a two-dimensional brand positioning graph using R. Besides positioning, this study also identified factors that are most influential in determining the choice of the cement brand selected by customers. The perceptual map showed three clear groups. Ambuja and UltraTech cement brands, which formed a group were preferred for major projects by engineers ; Wonder, Coromandel, and Binani cement brands formed another group ; and the rest of the brands clustered into a third group. JK brand appeared to be an outlier. This study also found that quality and brand reputation were the most influential factors in determining the brand choice. Price was a close third. We hope these findings would help both the manufacturers and the wholesalers with better consumer understanding to meet their expectations effectively.